PENGARUH KUALITAS LAYANAN, PROMOSI DAN EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION DI OENA EATERY - Nugraha, Kristian Agung (JURNAL ILMIAH EDUNOMIKA, 2025)
The hospitality industry is becoming more and more competitive, which forces hotel restaurants to give its customers experiences that are not only pleasurable but also unforgettable. Through emotional and sensory engagement, restaurants may cultivate patron loyalty by putting experience-based marketing methods into practice. To keep guests coming back, Oena Eatery, a restaurant inside the Grand Orchardz Hotel Jakarta, uses immersive marketing, high-quality service, and promotional activities. To find out how these elements affect consumers' decisions to make additional purchases, an evaluation is required. The purpose of this study is to investigate how Oena Eatery customers' intentions to repurchase are impacted by experiential marketing, service quality, and promotional activities. A quantitative research design was used, and 180 Jakartan residents who had at least one visit to Oena Eatery were given questionnaires to complete in order to collect data. The link between the independent and dependent variables was evaluated using multiple linear regression analysis. The findings show that repurchase intention is greatly influenced by experiential marketing, especially when it comes to the restaurant's atmosphere and satisfying dining experiences. Customer loyalty is also strengthened by high-quality service, particularly in terms of dependability and friendliness. Additionally, marketing campaigns like sales and themed gatherings help to promote return visits. According to the study's findings, repurchase intention is significantly impacted by experience marketing, service quality, and promotional activities taken together. Therefore, to increase Oena Eatery's competitiveness, constant experience-based marketing strategies, improved service quality, and creative promotional activities are essential.